Pemanfaatan Material Alami Dalam Dekorasi Upacara Manusa Yadnya di Desa Batubulan Kangin - I Wayan Arissusila; Anak Agung Ketut Raka; Ni Luh Putu Trisdyani (Jayapangus Press, 2022)
The decoration of the manusa yadnya ceremony at Batubulan Kangin is generally luxurious. The house is decorated from the entrance, to other buildings. In the past, to decorate houses that carried out the pawiwahan ceremony, synthetic materials were used, but with the 2018 Bali Governor Regulation, it emphasizes the prohibition of using synthetic materials and replacing them with natural materials. With these regulations, Batubulan Kangin craftsmen follow according to their imagination and creativity to produce artistic decorations. The decorations were accepted by the people of Batubulan Kangin, most importantly they still have a strong Balinese identity. This study uses a qualitative method with data collection through observation techniques on objects directly or indirectly, interviews with craftsmen and entrepreneurs, as well as document studies to collect data from books, village monographs, pictures and so on. The result is the decoration of the manusa yadnya ceremony at Batubulan Kangin using natural materials because of the Bali Governor's regulation which emphasizes the prohibition of using synthetic materials and replacing them with environmentally friendly materials. With these regulations, decoration craftsmen follow using natural materials and process them according to their imagination, resulting in artistic decorations. It does not violate the rules of the Balinese government. On the other hand, if the craftsmen continue to use synthetic materials, they will be subject to administrative sanctions. It is hoped that the decoration craftsmen comply with these rules, which are beneficial for the people and nature of Bali. The decoration products for the Manusa Yadnya ceremony that are created are decorations with the appearance of various shapes, variations of the decorations that appear in the form of woven mantri centipedes and a combination of gumitir flowers, pearls and so on. This decoration also depends on the selling value, consisting of: insulting, middle, main in the form of angkul-angkul decorations and aisle rides. While the implications can be classified into several parts, namely: economic implications, social status and environmental sustainability.